Arts Therapies Interventions and Their Outcomes in the Treatment of Eating Disorders: Scoping Review Protocol - Monika Bucharová; Andrea Malá; Jiří Kantor; Zuzana Svobodová (Behavioral Sciences, 2020)
Arts therapies (AsTs) are considered a valuable intervention for people with eating disorders, however the range of research studies and the comparison between the types of arts therapies are unknown. The goal of the future scoping review is to explore the therapeutic outcomes addressed by arts therapists in research studies on people with eating disorders and compare the different types of arts-based interventions. This scoping review will be conducted in accordance with the Joanna Briggs Institute methodology. Included will be research studies and sources oriented towards people with eating disorders of all ages and AsTs of any type (art therapy, drama therapy, music therapy, dance/movement therapy, and expressive therapies). There is no language/publication period limitation. The following databases will be searched: CINAHL Plus, EMBASE, MEDLINE (OvidSP), ProQuest Central, PsycINFO, PubMed, Scopus, and Web of Science. Sources of unpublished studies and grey literature will include Google Scholar, MedNar, clinical trials, and current controlled trials. Titles/abstracts and full texts of studies will be assessed against the inclusion criteria, and the data extracted by two independent reviewers. Based on the results, we will compare the types of AsTs according to the research designs, country/settings, intervention methods/materials, adverse effects reported, and therapeutic outcomes related to AsTs.